2021
DOI: 10.7759/cureus.15630
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lateral Internal Sphincterotomy in Haemorrhoidectomy: A Study in a Tertiary Care Center

Abstract: BackgroundHemorrhoids are a common condition that presents with bleeding per rectum, pain at rest and defecation, mucosal discharge, and prolapse. Surgical hemorrhoidectomy is the treatment method of choice for Grade 3 and Grade 4 hemorrhoids. Hemorrhoidectomy is associated with postoperative pain and no single surgical technique has been proved to significantly reduce the pain. We analyzed in our study the effect of lateral internal sphincterotomy with hemorrhoidectomy on postoperative pain, anorectal functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It has been observed in a few randomized controlled trials that hemorrhoidectomy in combination with lateral internal sphincterotomy resultsin relatively decreased postoperative pain and improved wound healing. 13,14 The outcome of this study is comparable with a study revealing that mean post-operative pain score in patients with open hemorrhoidectomy combined with internal sphincterotomy was 1.60±0.8 and in patients with open hemorrhoidectomy alone it was 2.32±1.16 at first 48 hours, with a P-value <0.01. Likewise, early complications including urinary retention and pain during first bowel motion after surgery were also significantly low (P<0.01) in the hemorrhoidectomy with sphincterotomy group when compared to the control group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It has been observed in a few randomized controlled trials that hemorrhoidectomy in combination with lateral internal sphincterotomy resultsin relatively decreased postoperative pain and improved wound healing. 13,14 The outcome of this study is comparable with a study revealing that mean post-operative pain score in patients with open hemorrhoidectomy combined with internal sphincterotomy was 1.60±0.8 and in patients with open hemorrhoidectomy alone it was 2.32±1.16 at first 48 hours, with a P-value <0.01. Likewise, early complications including urinary retention and pain during first bowel motion after surgery were also significantly low (P<0.01) in the hemorrhoidectomy with sphincterotomy group when compared to the control group.…”
Section: Discussionsupporting
confidence: 83%
“…A study concluded on the point that post operative wound healing, pain and other complications were lesser in patients in whom lateral internal sphincterotomy was combined with hemorrhoidectomy to treat haemorrhoids. 13 A study by Vijayaraghavalu and Rajkumar 14 showed that the pain 12 hours post operatively after hemorrhoidectomy with lateral internal sphincterotomy is 5.1±1.9 as compared 6.12±2.3. This difference is statistically significant (p<0.0008).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a significant higher rate of fecal incontinence in patients with LIS compared with those without (7.7% versus 1.25%), although the severity of fecal incontinence was mild (e.g., flatus incontinence and fecal soiling) and improved over time [ 35 ]. In 2021, a single-institute RCT of 200 patients from India also confirmed the efficacy of LIS on better pain relief after hemorrhoidectomy, without compromising anal continence [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies compared routine haemorrhoidectomy with lateral internal sphincterotomy (LIS) against haemorrhoidectomy without LIS [45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Lateral Internal Sphincterotomy (Lis)mentioning
confidence: 99%